2007
DOI: 10.1002/adsc.200600505
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO‐Copper(II) Diimine‐Catalysed Oxidation of Benzylic Alcohols in Aqueous Media

Abstract: In situ generated copper(II)-diimine complexes combined with TEMPO (2,2,6,6-tetramethylpiperidinyl-1-oxyl radical) were studied in the oxidation of benzylic alcohols, the focus being on enviromentally benign reaction conditions. In this respect, reactions were studied in aqueous alkaline solutions and dioxygen was used as an end oxidant. This simple catalytic system turned out to be highly efficient and selective in the oxidation of primary and secondary benzylic alcohols to their corresponding carbonyl compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(62 citation statements)
references
References 11 publications
3
58
1
Order By: Relevance
“…The very similar catalytic activities of 1-3 are in accord with their very similar reduction potentials as detected by cyclic voltammetry (see above), which conceivably determine the iron promoted decomposition of TBHP (see mechanistic considerations below) [39,40].…”
Section: Microwave-assisted Catalytic Peroxidativesupporting
confidence: 51%
“…The very similar catalytic activities of 1-3 are in accord with their very similar reduction potentials as detected by cyclic voltammetry (see above), which conceivably determine the iron promoted decomposition of TBHP (see mechanistic considerations below) [39,40].…”
Section: Microwave-assisted Catalytic Peroxidativesupporting
confidence: 51%
“…More recently, Repo and coworkers [117] showed that the selective aerobic oxidation of benzyl alcohol to benzaldehyde could be performed with TEMPO in combination with Cu(II)/phenanthroline in aqueous alkaline with no added organic solvent. Finally, an interesting recent development in copper-catalyzed oxidation of alcohols is the use of copper nanoparticles on hydrotalcite as a heterogeneous catalyst for the liquid phase dehydrogenation of alcohols in the absence of an oxidant [118].…”
Section: ð5:15þmentioning
confidence: 99%
“…2-furylmethanol) under an oxygen atmosphere [38]. Repo et al recently reported a highly efficient catalytic system based on TEMPO/Copper diimine (10 bar oxygen) and 2-Narylpyrrolecarbaldimino (1 atm oxygen) systems for alcohol oxidation [39][40]. In recent studies, Koskinen et al and Stahl et al have described improved bipyridine-Cu-TEMPO catalytic systems for the effective oxidation of alcohols [41][42].…”
Section: Introductionmentioning
confidence: 99%